2014
DOI: 10.1063/1.4872017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an ITER-like wall on disruptions at JET

Abstract: In order to preserve the integrity of large tokamaks such as ITER, the number of disruptions has to be limited. JET has operated previously with a low frequency of disruptions (i.e. disruption rate) of 3.4% [P.C. de Vries, et al., Nucl. Fusion 51 (2011) 053018]. The start of operations with the new full-metal ITER-like wall at JET showed a marked rise in the disruption rate to 10%. A full survey was carried out to identify the root causes, the chain-of-events and classifying each disruption, similar to a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 25 publications
2
69
0
Order By: Relevance
“…Introduction: A study of the root causes of disruptions in the JET tokamak found that neoclassical tearing modes (NTMs) were the single most common cause [1,2]. Theoretical calculations in the early 1980's showed the feasibility of using rf current drive to stabilize tearing modes [3,4].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Introduction: A study of the root causes of disruptions in the JET tokamak found that neoclassical tearing modes (NTMs) were the single most common cause [1,2]. Theoretical calculations in the early 1980's showed the feasibility of using rf current drive to stabilize tearing modes [3,4].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…NTMs were recognised as a source of major disruptions in experiments such as JET 6,7 , and thus their stabilisation is central. Amongst proposed stabilisation approaches, driving current 8,9 at the islands with RF waves has stimulated a long list of added efforts, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] including many experimental demonstrations [30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…If all of the latter events were to lead to the termination of the plasma, this would translate in a 0.8% TIE-induced plasma termination rate. This is a factor 4 lower than the unintentional disruption rate observed in the last years of JET-C (3.4%) and an order of magnitude lower than the rate observed in the 2011-2012 JET-ILW campaigns (10%) [6].…”
Section: Impact On Plasma Operation and Parametric Dependenciesmentioning
confidence: 96%
“…The limited amount of TIE-induced disruptions are not reported since they have been intensively analyzed elsewhere (see e.g. [6]). Modeling of the particle ablation has been performed using the dust code DTOKS [7].…”
Section: Introductionmentioning
confidence: 98%